A numerical analysis of ventilation motion after chest surgery with a RESPIRholter device - Marco Ceccarelli; Manuel D'Onofrio; Vincenzo Ambrogi; Matteo Russo (Respiratory Medicine Case Reports, 2024)
This case report presents a numerical evaluation of respiration in terms of biomechanical parameters of chest motion. This experimental evaluation is performed with RESPIRholter, a wearable device specifically developed to monitor the movement in the ribcage through the motion of the sixth rib whose characteristic motion is considered as representative of the motion of the thorax. Here we present test results acquired with a RESPIRholter device in a 6-h acquisition. These results characterize respiration biomechanics for diagnostic purposes in a chest surgery patient, highlighting the diagnostic utility of RESPIRholter in the identification of post-operation respiratory problem.